2019
DOI: 10.1017/s0022215119000690
|View full text |Cite
|
Sign up to set email alerts
|

Management of subglottic stenosis in pregnancy using advanced apnoeic ventilatory techniques

Abstract: ObjectiveTo describe the use of balloon dilation with non-invasive ventilation in the treatment of pregnant patients with idiopathic subglottic stenosis.MethodsThe medical charts of four consecutive patients who underwent jet ventilation or high-flow nasal cannula oxygenation with balloon dilation for the treatment of idiopathic subglottic stenosis during pregnancy were reviewed.ResultsObjective improvement of subglottic stenosis was seen in all four cases, with end-result Myer–Cotton grade 1 lesions down from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
(33 reference statements)
1
28
0
Order By: Relevance
“…The study of Mir ( 19 ) showed that THRIVE was a practical method for pre-oxygenating patients for rapid sequence induction. HFNO can also be used in patients with airway stenosis ( 8 ), such as subglottic stenosis ( 9 11 ) and tracheal stenosis caused by thyroid tumor ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Mir ( 19 ) showed that THRIVE was a practical method for pre-oxygenating patients for rapid sequence induction. HFNO can also be used in patients with airway stenosis ( 8 ), such as subglottic stenosis ( 9 11 ) and tracheal stenosis caused by thyroid tumor ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Current studies use the subjective Cotton-Myer grade or estimated percent obstruction (% stenosis) as the exclusive objective outcome measure in the management of adult subglottic stenosis. [5][6][7] These studies assume that endoscopic grading is sufficient in following patients with subglottic stenosis.…”
mentioning
confidence: 99%
“…The presence of subglottic stenosis in pregnant women is significant and rare, and may lead to a life-threatening delivery; 2 management therefore requires expertise. Damrose and colleagues 3 describe their use of balloon dilatation with non-invasive ventilation techniques in the treatment of pregnant patients with idiopathic subglottic stenosis. There is limited experience in the management of this condition, so this paper is an excellent addition to our knowledge.…”
mentioning
confidence: 99%